(untitled) (Journal of Scientific Research, 2024)
Butterfly Pea (Clitoria ternatea Linn.), renowned in traditional medicine across diverse cultures, is explored in this study for its pharmacological and phytochemical aspects. Focusing on blue and white varieties from Kerala, India, the research compares elemental phytochemistry and pharmacological activities of aqueous extracts. The plant’s medicinal applications, from Ayurvedic treatments to culinary uses, are highlighted. The investigation identifies the White variant as beneficial for bone health, while the blue variant offers antioxidant, antidiabetic, and antifungal properties. The study emphasizes Butterfly Pea flower tea as a caffeine-free alternative with diverse therapeutic potentials for health-conscious individuals.